CAUSAS DOS ACIDENTES DE TRABALHO EM IMPLEMENTAÇÃO DE EMPREENDIMENTOS PARA ÁREA DE REFINO: UM ESTUDO DE CASO - Moura, Elton Saturnino Campos de (2010)
The sustainability of a project depends, among other factors, on a wellimplemented and consistent safety management system - for there may be some impact on the deadline, cost, productivity, as well as damage to the company s reputation if the elements related to labor safety are badly managed. However, although labor safety is extremely important, it is not valued by most companies as much as it should, even after the recent changes in legislation. An adequate study on labor injuries provides a precious source of knowledge, so it s manager s role assure investigation on every injury and learn from it. Afterwards, preventing steps must be taken so as to stop the causes of injuries, rather than its effects. As a result, it will promote the sustainable reduction in labor injuries. Therefore, this research lists the injuries occurred in an important construction between 2002 and 2009, establishing a relation to the advance in legislation, the organization of the companies involved and the methods of injury investigation used. It was also necessary to investigate why the workers behaved differently before equally risky situations. Furthermore, several local workers were interviewed, and a study was done, in which 2276 workers were questioned. An academic study on the local safety was also considered. The study showed that the analysis of the injuries, several times, still blames workers for the occurrence, and that in many cases the causes of the injuries and incidents are not correctly identified. Even on cases which the worker s safety and health management system does not establish the necessary blocking measures, the manager is not adequately considered responsible.